Respuesta :
Answer:
3(y - 3) + 2y = 7
Step-by-step explanation:
To get your answer, first change the second equation so that it will equal x. Add y to both sides and then subtract 3 from both sides, and you will get
x = y - 3. Next, substitute that equation in for x in the first equation. You will get 3(y - 3) + 2y = 7.
After substitution from equation 2, the first equation will be [tex]3(y-3) + 2y = 7[/tex]. Option B is correct.
Given information:
The given system of equations is,
[tex]3x + 2y = 7\\x - y + 3 = 0[/tex]
Use the second equation to make a substitution for x in the first equation,
[tex]3x + 2y = 7\\x - y + 3 = 0\\x=y-3\\3x + 2y = 7\\3(y-3) + 2y = 7[/tex]
Using the required substitution, the equation will be [tex]3(y-3) + 2y = 7[/tex].
Therefore, after substitution from equation 2, the first equation will be [tex]3(y-3) + 2y = 7[/tex]. Option B is correct.
For more details, refer to the link:
https://brainly.com/question/22340165